DNA damage repair-related gene signature predicts prognosis and indicates immune cell infiltration landscape in skin cutaneous melanoma - Liang, Liping; Mai, Shijie; Mai, Genghui; Chen, Ye; Liu, Le (Frontiers in Endocrinology, 2022)
Background: DNA damage repair performs an instrumental function in the onset and development of cancer as well as its resistance to treatment. This research examined the prognostic potential of DNA damage repair indicators in skin cutaneous melanoma (SKCM). Method: Gene expression profiles downloaded from The Cancer Genome Atlas (TCGA), genotype-tissue expression (GTEx) and Gene Expression Omnibus (GEO) databases were analyzed. In order to screen DNA repair genes in relation to the prognosis, univariate and LASSO Cox regression analyses were sequentially utilized. Next, a multivariate regression analysis was conducted to construct the prognostic profile of DNA repair-related genes (DRRGs). We utilized the risk coefficient to compute the risk score and divide the patients into two cohorts. We also validated the prognosis model in an external cohort. Additionally, we evaluated the link between immune response and the DRRGs prognostic profiles. The correlation of risk signature with immune infiltration, immune checkpoint blockade (ICB) therapy and chemotherapy was also analyzed. Result: A prognostic signature that comprised twelve DRRGs and had good predictive capacity was established by LASSO–Cox stepwise regression analysis. High-risk patients were found to have significantly shorter OS than patients in low-risk group. The signature can be used as an independent prognostic predictor after adjusting for clinicopathological parameters, and was validated on one external GSE65904 cohort. Besides, the risk score significantly correlated with immune score, immune-related signature, infiltrating immune cells, and ICB key molecules. Gene enrichment analysis indicated that multiple biological behaviors and pathways were active in the high-risk group. Cisplatin exhibited a considerable response sensitivity in high-risk incidents as opposed to the low-risk incidents, while docetaxel exhibited a considerable response sensitivity in low-risk incidents Conclusions: The findings provide a systematic analysis of DRRGs and develop an OS-related prognostic predictor which are useful in forecasting SKCM progression and the clinical benefits of immunotherapy.